Światło i jego ekwiwalenty w wybranych utworach ostatniego okresu twórczości Juliusza Słowackiego - Ciechańska, Magdalena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
One of the basic components of the world created by Juliusz Słowacki in his late works is the light. In the poet’s mystical work the light is closely connected with the sphere of the sacrum, which is directly unapproachable for the ghost imprisoned in matter. On the night April of 20th and 21st in 1845 the poet experienced mystical vision, so called vision of the fiery. God reveals himself to a passive subject not in the light, but in the fire, fiendish streak. The first part of the article is an attempt to answer the question why in Juliusz Słowacki’s mystical work God reveals in fire, which is fiendish streak, and not in sanctifying light. In the second part the position of colours in the Genesis universe and their relation with the light was described.